The family interest and its legal relevance for the purpose of the VIII Plenary casatory - Del Aguila Llanos, Juan Carlos (2020)
The author analyzes the importance of remembering the existence of interests within the family as a basis to resolve the various conflicts that may occur within the framework of family relationships and even to face the legal gaps that may exist in the regulations that regulate these relationships relatives, as it considers that a systematic interpretation of the specialized norm should be applied, respecting the particularity of Family Law, leaving behind the thought that everything should be resolved only by observing criteria applicable to general norms of Civil Law. This issue is approached from the decision adopted by a majority in the eighth eighth plenary session civil which determined that the non-intervention of both spouses in the provision of a social good is null.